Activity Based Costing Method in Determining Tariffs at Waikabubak Regional Hospital, West Sumba-NTT - Herlina, Nina -; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2024)
The researcher took the thesis title 'Activity Based Costing Method in Determining Tariffs at Waikabubak Regional Hospital, West Sumba-NTT' because health service rates at Waikabubak Regional Hospital have not been determined based on unit cost analysis using the activity-based costing method (Analysis Base Costing). Researchers want to see a comparison of the calculation of the Activity Base Costing Method in the Intensive Care Unit at the Waikabubak-NTT Regional Hospital with the calculation of hospital rates based on West Sumba Regent Regulation Number 45 of 2021 concerning Service Tariffs at the Regional Public Service Agency at the Waikabubak Regional General Hospital. So this research aims to provide knowledge and recommendations regarding the calculation of rates in the ICU for cases of heart disease using the ABC method and to analyze the differences in the results of calculating the unit cost of the ABC method with the current rates for ICU rooms at the Waikabubak-NTT Regional Hospital. The research method is qualitative with a descriptive case study design. This research uses primary data and secondary data. Primary data is in the form of interview results, while secondary data is obtained through account data of ICU patients treated from January to June 2023. And the theoretical basis for analyzing costs uses the Activity Based Costing (ABC) method. The calculation results of the ICU room hospitalization rate are Rp. 460,655.00 using the Activity Based Costing (ABC) method which is a price difference of Rp. 89,345.00 compared to the hospital's calculation of Rp. 550,000.00.Key words: activity based costing, ICU room hospitalization rates, ina-CBGs, methods used by regional general hospitals.